2017
DOI: 10.1164/rccm.201604-0668oc
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Lung Injury Reduces Krüppel-like Factor 2 to Increase Endothelial Permeability via Regulation of RAPGEF3–Rac1 Signaling

Abstract: Disruption of endothelial KLF2 results in dysregulation of lung microvascular homeostasis and contributes to lung pathology in ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 54 publications
(63 reference statements)
1
53
0
Order By: Relevance
“…Thus, an optimal level of miR‐483 in pulmonary endothelium may mitigate PAH‐related EC dysfunction. Indeed, miR‐483 overexpression in cultured PAECs induced the expression of genes critical for EC homeostasis that include Krüppel‐like factor 2 (KLF2), KLF4, eNOS, ACE2, and APLNR (; Shen et al , ; Alastalo et al , ; Huang et al , ; Zhang et al , ). Interestingly, KLF4 overexpression, statins treatment, and pulsatile shear stress, known to enhance endothelial function, also increase the expression of miR‐483 in ECs (He et al , ; Fernandez Esmerats et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an optimal level of miR‐483 in pulmonary endothelium may mitigate PAH‐related EC dysfunction. Indeed, miR‐483 overexpression in cultured PAECs induced the expression of genes critical for EC homeostasis that include Krüppel‐like factor 2 (KLF2), KLF4, eNOS, ACE2, and APLNR (; Shen et al , ; Alastalo et al , ; Huang et al , ; Zhang et al , ). Interestingly, KLF4 overexpression, statins treatment, and pulsatile shear stress, known to enhance endothelial function, also increase the expression of miR‐483 in ECs (He et al , ; Fernandez Esmerats et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Highly interconnected networks are predicted to represent a significant biological function [23] . IPA was used to connect 132 genome-wide association study (GWAS)- implicated cancer genes along with microRNA and various cancer pathways [ 24 , 25 ]. Significantly changed miRNAs associated with Akt1 inhibition from the two experimental sets were uploaded in IPA and core analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that thyroid hormone and glucocorticoid receptors are important mediators in lung development and KLF2 is a necessary regulator for thyroid hormone and silencing mediator of retinoid and thyroid hormone receptors (SMRT)-mediated maturation of type I pneumocytes in the lung [ 17 ]. It has been also shown that lung KLF2 expression is significantly reduced in vivo rodent models on exposure to acute lung injury by influenza virus, lipopolysaccharides (LPS), or high-tidal-volume mechanical ventilation [ 18 ]. Endothelial barrier integrity is maintained by KLF2 and guanine nucleotide exchange factor 3 (RAPGEF3)-Ras-related C3 botulinum toxin substrate (RAC)1-mediated signaling.…”
Section: Kruppel Like Factormentioning
confidence: 99%